Analysis of connected air voids in warm mix asphalt (2012)
Warm mix asphalt (WMA) are asphalt mixtures produced at reduced temperatures as compared to conventional hot mix asphalt (HMA). Temperature reductions in the order of 10 to 50 C are possible through the incorporation of diverse WMA type additives. However, different aspects, including the mixture internal structure of WMA, are still object of research. Consequently, this paper focused on the assessment of the internal structure of WMA (computed in terms of the Connected Air Voids (CAV) characteristics), fabricated using three WMA additives: Asphamin®, Sasobit®, and Evotherm®. The CAV content corresponds to the fraction of Air Voids (AV) forming connected paths in a compacted specimen and is better related to the asphalt mixture response (e.g., permeability) than the total AV content. The CAV analysis was based on X-ray Computed Tomography scanning and subsequent image analysis. Corresponding results suggested the need of additional research to further characterize field compacted mixtures, produced at densification levels comparable to those achieved in the laboratory. In addition, the inclusion of WMA additives and corresponding temperature reductions did not substantially affect the internal structure of gyratory-compacted specimens (115 mm in height) produced for laboratory mixture evaluation.